Tinjauan Asas Pemaafan dalam Perspektif Hukum Islam dan Hukum Indonesia pada Perkara Tindak Pidana Pembunuhan - Muhammad Muslih Hisyam; Ufran Ufran (Indonesia Berdaya, 2023)
The purposes of this study are, firstly, to find out how the regulation of the crime of murder in Islamic law and the Criminal Code, and secondly, to figure out the principle of non-imposing penalty for the crime of murder in Islamic law and Indonesian Criminal Law. This research uses normative legal analysis. The results of this study explain how the regulation of the crime of murder in Islamic law and Indonesian law, and how the principle of non-imposing penaltyfor the crime of murder in Islamic Criminal Law and Indonesian Criminal Law.